The Influence of Direct Reduced Iron Size on EAF Smelting - Kang Xu, Cao Zhenwei, Wang Qiang, Liu Chong, Li Shuangjiang, Zhang Junfen (Teshugang)
Taking the 40Cr steel smelted by Consteel EAF of Zhang Xuan Technology as the research object， the effects of adding different particle size direct reduced iron （DRI） to the Consteel EAF on the EAF smelting process， steel material consumption， electricity consumption， and final slag ingredient of the EAF were studied by conducting experiments on adding 30 tons of different particle size DRI to the EAF. The results indicate that adding small-sized DRI during the smelting of 40Cr steel in an EAF can easily lead to an increase in slag overflow during the smelting process， and the FeO content in the overflow slag is higher， resulting in an increase in steel and electricity consumption， a decrease in the alkalinity of the final slag， and an increase in the FeO content of the final slag. At the same time， the slag discharged from the EAF with small-sized DRI is prone to forming iron thallium at the bottom of the slag tank. When small-sized DRI falls from the top of the EAF， the impact force is relatively small and cannot pass through the slag layer to remain in the slag layer. The small-sized DRI retained in some slag and the small steel droplets formed after melting of small-sized DRI flow out with the overflow slag at the furnace door. The steel droplets inside the slag in the slag tank continuously sink through the slag layer and bond to the bottom of the slag tank， continuously increasing to form iron and thallium. The proportion of EAF smelting 40Cr steel with DRI size ≤ 6.3 mm is less than 8.5%， and the smelting effect is better， DRI can be screened and used to remove those with smaller particle sizes. At the same time， avoid loading materials from empty silos， try to load materials in half or above half silos， and avoid large drop DRI crushing that increases the proportion of small particles.